2020
DOI: 10.3390/jfb11030063
|View full text |Cite
|
Sign up to set email alerts
|

Carbonate Apatite and Hydroxyapatite Formulated with Minimal Ingredients to Deliver SiRNA into Breast Cancer Cells In Vitro and In Vivo

Abstract: Introduction: Cancer is one of the top-ranked noncommunicable diseases causing deaths to nine million people and affecting almost double worldwide in 2018. Tremendous advancement in surgery, chemotherapy, radiation and targeted immunotherapy have improved the rate of cure and disease-free survival. As genetic mutations vary in different cancers, potential of customized treatment to silence the problem gene/s at the translational level is being explored too. Yet delivering therapeutics at the required dosage on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 54 publications
(64 reference statements)
0
11
0
Order By: Relevance
“…A study by Islam et al demonstrated that upon systemic delivery, NPs come into interaction with serum proteins, forming a protein corona (PC). The composition of PC depends on size, charge and other physicochemical features of NPs, and in in vivo mouse studies, the PC can be remodeled with the change of proteome in different treatment formulations [28,52,53]. Another possibility of epigenetic changes in in vivo environment may affect gene expression and protein interaction in different treatment groups; hence, future study might focus on the in vivo mechanism of the combined therapy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A study by Islam et al demonstrated that upon systemic delivery, NPs come into interaction with serum proteins, forming a protein corona (PC). The composition of PC depends on size, charge and other physicochemical features of NPs, and in in vivo mouse studies, the PC can be remodeled with the change of proteome in different treatment formulations [28,52,53]. Another possibility of epigenetic changes in in vivo environment may affect gene expression and protein interaction in different treatment groups; hence, future study might focus on the in vivo mechanism of the combined therapy.…”
Section: Discussionmentioning
confidence: 99%
“…As our NPs contain both positive and negative ions, such as Ca 2+ , PO 4 3− , OH − , the negative charge may come from the protein corona formed around the NPs in serum-containing media. In fact, a recent study revealed that at physiological pH, CA NPs attach to both positive and negative proteins; however, the negative proteins outnumbered the positive ones, which could contribute to the negative zeta potential [28]. Negative zeta potential is advantageous in terms of longer retention in blood stream [34].…”
Section: Size and Zeta Potential Of Prkca Specific Sirna-and Pten Plasmid-loaded Npsmentioning
confidence: 99%
See 2 more Smart Citations
“…HAP/magnetic NP composites are promising biomaterials for targeted drug delivery systems [ 15 ], for example, for orthopedic drugs, and the protein adsorption/controlled pH-dependent release of antitumor drugs [ 16 , 17 , 18 ]. New areas of potential application are gene therapy [ 19 , 20 ], antibacterial nanocomposites, and composites for implants [ 21 ]. The combined effect of magnetic and hydroxyapatite nanostructures provides a high loading capacity of a drug compound and its efficient delivery to targets under the influence of external magnetic fields.…”
Section: Introductionmentioning
confidence: 99%